Microbiology and antimicrobial sensitivity of ventriculo-peritoneal shunt infections in a referral paediatric neurosurgery ward during a period of 7 years - Sayed Nassereddin Mostafavi; Majid Khedmati; Roya Kelishadi (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: This study aims to evaluate the aetiology and antibiotic susceptibility pattern in children with ventriculo-peritoneal (VP) shunt infections. Methods: A retrospective investigation was conducted from March 2011 to March 2018 among 163 children, who were admitted because of VP shunt infections in a referral educational hospital in Isfahan, Iran. Results: Coagulase negative staphylococcus (CoNS) was the most common organism (49.0%), followed by Acinetobacter baumannii (10.4%) and Staphylococcus aureus (8.9%).Susceptibility of Gram-positive organisms to a different class of antibiotics was as follows: glycopeptides (82, 96%), carbapenems (78.38%), aminoglycosides (57.81%), fluoroquinolones (50.00%) and trimethoprim-sulfamethoxazole (50%). Gram-negative isolates were more susceptible to aminoglycosides (56.52%) and fluoroquinolones (52.78%), respectively. Sensitivity of Gram-negative bacteria to fluoroquinolones was significantly higher in infections that occurred in the first month of the shunt implantations compared to infections that were detected afterward (78.95% vs. 23.53%, respectively, P = 0.001). Conclusion: The highest sensitivity of Gram-positive bacteria was to glycopeptides and carbapenems. In addition, Gram-negative organisms had the best susceptibility to aminoglycosides and fluoroquinolones. A high level of resistance to studied antibiotics among Gram-negative isolates underscores the necessity of including new antibiotics such as colistin, fosfomycin, ceftazidime/avibactam, ceftolozane/tazobactam and tigecycline in susceptibility testing and empiric antibiotic therapy for VP shunt infections.